Dental trauma in a patient with autism spectrum disorder. Clinical case report - Cançado Figueiredo, Márcia (2022)
A 12-year-old girl diagnosed with autism spectrum disorder (ASD), epilepsy, and intellectual deficit, was seen at the dental clinic for patients with special needs at the Dental School of the Federal University of Rio Grande do Sul, due to a gingival hemorrhage on tooth 21, after a fall due to a seizure. The clinical examination of the patient identified active caries and the presence of visible biofilm on almost all dental surfaces. A radiographic exam of tooth 21 showed a fracture in the middle-third root of the tooth. All the necessary dental procedures were carried out during the endodontic treatment on tooth 21, filling the canal with calcium hydroxide paste. During the beginning of the care, the patient presented an agitated behavior requiring specialized management, always keeping the caregiver in the same clinical setting so that the patient felt welcomed. It concluded the knowledge of the particularities of the patient-reported with ASD was of utmost importance for the conduct of her dental treatment, enabling appropriate behaviors in her rehabilitation.